Relation between senior managers' safety leadership and safety behavior in the Chinese petrochemical industry. (May 2020) - Xue, Yujingyang; Fan, Yunxiao; Xie, Xuecai
Abstract: Senior managers in organizations are authorized and obliged to maintain organizational safety. However, to date, little research has considered the relation of senior managers' safety leadership to safety behavior. This study addresses this gap by using path analysis to confirm the validity of a hypothetical model that relates six dimensions of senior managers' safety leadership to two safety behaviors through the safety climate in the petrochemical industry. A questionnaire survey was sent randomly to workers (other than senior managers) in two petrochemical companies in China, and data from 155 usable responses were compiled for the path analysis. Results indicate that in the petrochemical industry, senior managers' safety leadership has a positive impact on safety behavior, and the safety climate plays an intermediary role between them. From the perspective of the dimensions of senior managers' safety leadership and safety behavior, safety concern has the greatest positive effect on safety compliance. Moreover, safety vision has the greatest positive impact on safety participation, whereas safety inspiration and safety awards and punishment have negative effects on safety compliance. Personal character does not directly influence any dimension of safety behavior but indirectly does so by influencing the safety climate. On the basis of these results, measures of improving senior managers' safety leadership in the petrochemical industry are presented to help improve the overall safety performance of the industry. A new view is provided for the petrochemical industry in China to suggest that senior managers' safety leadership can be treated earnestly. Highlights: Six subdimensions of senior managers' safety leadership based on Chinese petrochemical industry were proposed. Senior managers' safety leadership had a positive impact on safety behavior in Chinese petrochemical industry. Safety climate played an intermediary role between senior managers' safety leadership and safety behavior. Mechanism of 6 subdimensions of senior managers' safety leadership and 2 subdimensions of safety behavior was clarified. Senior managers should pay more attention to the construction of their safety leadership in process safety management.